Complex genetic and histopathological study of 15 patient-derived xenografts of aggressive lymphomas - Jakša, Radek; Karolová, Jana; Svatoň, Michael; Kazantsev, Dmitry; Grajciarová, Martina; Pokorná, Eva; Tonar, Zbyněk; Klánová, Magdalena; Winkowska, Lucie; Maláriková, Diana; Vočková, Petra; Forsterová, Kristina; et al. (Laboratory investigation, 2022)
Non-Hodgkin lymphomas (NHL) represent the most common hematologic malignancies. Patient-derived xenografts (PDXs) are used for various aspects of translational research including preclinical in vivo validation of experimental treatment approaches. While it was repeatedly demonstrated that PDXs keep majority of somatic mutations with the primary lymphoma samples, from which they were derived, the composition of PDX tumor microenvironment (TME) has not been extensively studied. We carried out a comparative genetic and histopathological study of 15 PDX models derived from patients with various types of NHL including diffuse large B-cell lymphoma (DLBCL; n = 7), Burkitt lymphoma (BL; n = 1), mantle cell lymphoma (MCL; n = 2), and peripheral T-cell lymphomas (PTCL; n = 5). Whole exome sequencing (WES) of the PDXs and primary lymphoma cells was implemented in 13 out of 15 cases with available DNA samples. Standard immunohistochemistry (IHC) was used to analyze the composition of PDX TME. WES data confirmed that PDXs maintained the genetic heterogeneity with the original primary lymphoma cells. In contrast, IHC analysis revealed the following recurrently observed alterations in the composition of PDX tumors: more blastoid lymphoma cell morphology, increased proliferation rate, lack of non-malignant cellular components including T cells and (human or murine) macrophages, and significantly lower intratumoral microvessel density and microvessel area composed of murine vessels. In addition, PDX tumors derived from T-NHL displayed additional differences compared to the primary lymphoma samples including markedly lower desmoplasia (i.e., the extent of both reticular and collagen fibrosis), loss of expression of cytotoxic granules (i.e., perforin, TIA, granzyme B), or loss of expression of T-cell specific antigens (i.e., CD3, CD4, CD8). Our data suggest that despite keeping the same genetic profiles, PDX models of aggressive NHL do not recapitulate the microenvironmental heterogeneity of the original lymphomas. These findings have implications on the relevance of PDX models in the context of preclinical research.
Keywords: imunohistochemie; Lymphoma, Large B-Cell, Diffuse; dospělí; Animals; nádorové mikroprostředí; Humans; Immunohistochemistry; Tumor Microenvironment; lidé; zvířata; Mice; Antineoplastic Agents; protinádorové látky; difúzní velkobuněčný B-lymfom; Adult; myši